Characterisation of the corticospinal tract using Diffusion Magnetic Resonance imaging in Unilateral and Bilateral Cerebral Palsy patients - Safwan Samsir; Rahimah Zakaria; Salmi abdul razak; Mohamed Saat Ismail; Mohd Zulkifli abdul rahim; Chia-Shu lin; Nik Mohammad Faez Nik Osman; Mohammad Afiq Asri; Asma Hayati Ahmad (UniversitI Sains Malaysia, 2018)
Neuroimaging is increasingly used to locate the lesion that causes cerebralpalsy (CP) and its extent in the brains of CP patients. Conventional structural magnetic resonanceimaging (MRI) does not indicate the connectional pattern of white matter; however, with the helpof diffusion MRI, fibre tracking of white matter can be done.Methods: We used diffusion MRI and probabilistic tractography to identify the putativewhite matter connectivity in the brains of 10 CP patients. We tracked the corticospinal tract (CST)of the patients’ upper and lower limbs and calculated the white matter connectivity, as indexed bystreamlines representing the probability of connection of the CST.Results: Our results show that diffusion MRI with probabilistic tractography, while havingsome relation with the clinical diagnosis of CP, reveals a high degree of individual variation in thestreamlines representing the CST for upper and lower limbs.Conclusion: Diffusion MRI with probabilistic tractography provides the state ofconnectivity from lesioned areas to other parts of the brain and is potentially beneficial to beused as an adjunct to the clinical management of CP, providing a means to monitor interventionoutcomes.